ادمان شبکة الانترنت وأضرارها الصحیة والنفسیة والاجتماعیة على طلاب المدارس الثانویة بمدینة شبین الکوم بمحافظة المنوفیة - د. میرفت مفید عبد الستار (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aimed to identify the health, psychological and social damagesof internet addiction among secondary school students, through the identificationof the damages of Internet addiction on adolescence and its social, psychologicaland health effects on them. The most important results and recommendationsreached by the researcher through the field study in public secondary schools inShebin El-Kom city, Monofiya governorate, Egypt.The Results of the studyThe researcher reached many results as follows:-1. 1-The main causes of addiction to the students of secondary education forthe Internet Monofiya, the following respectively: entertainment and play,lack of control parents to me, a sense of vacuum time, ease of dealingwith others through the Internet, sense of comfort while using the Internet,to escape from the responsibility to study and study, not My interest onthe part of the family and the community around me, to escape from myproblems surrounding the family, rather than going out2. 2- The largest percentage of students addicted to the Internet in the agegroup of 16 years reached 102 respondents, representing 56.7% of thetotal male and female population in the study sample.3. .3- The most important negative aspects of the internet came between hisstudents and secondary education students in Monofiya, respectively:lack of supervision, porn sites, addiction to sit for long periods, violation ofrights, falling into unknown relationships, exposure to fraud and fraud.4. 4- came the most important health damage caused by Internet addictionamong education students secondary Monofiya: pain the eyes of the mostdifficult and the most first health damage caused by the use of the Internetamong students at a percentage of 60.5%, followed by insomnia andsleep deprivation, a percentage of 50.4%, followed by fatigue and fatigueby 49.7 %, mother bone by 45.7%, and diseases of the brain and nerves30.2%, heart disease by 22.7%, and finally skin diseases by 21.5% of thetotal sample.